Equivocal Economic Terms or Terminology Revisited - Resche, Catherine (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractThis paper on a category of oddly flexible terms found in social sciences such as economics that seem to call into question the fundamental principles of well-defined terminology. The first part is devoted to particularly deceptive terms either because their meaning varies over time, although they appear unchanged, or because the relation between the signifiant and the signifié is stretched beyond recognition. The second part examines various linguistic or rhetorical techniques such as neologisms, euphemisms, metaphors, oxymorons and reductions that lead to the blurring of notions and meanings. Finally, the causes that allow such loose terminology to arise are investigated. The need to record and identify the evolution of these fuzzy terms is all the more pressing as foreign students of English as well as translators have to be guided around the pitfalls and be given a chance to improve their mastery of all the aspects of a given terminology.